GRAMMATICAL MARKEDNESS OF NON-VERBAL CONSTRUCTIONS IN MINANGKABAUNESE: A Grammatical Typological Study - Jufrizal Jufrizal (Linguistik Indonesia, 2022)
The markedness theory has been becoming an important tool to directly link formal (structural) linguistic data and properties across languages. Markedness is one of the criteria which is used to determine the asymmetry of grammatical constructions in languages being learnt. So far, typological analyses on the non-verbal grammatical constructions in Minangkabaunese[1] have not been particularly based on the markedness theory yet. Therefore, the markedness analysis on the grammatical constructions of Minangkabaunese is linguistically meaningful. This article specifically analyzes and discusses the markedness values of the non-verbalÂ  constructions in Minangkabaunese based on markedness theories developed and used in Linguistic Typology. Two questions as the basis for data analysis and discussion are: (i) what are the unmarked and marked non-verbal constructions of Minangkabaunese based on formal and functional markedness analysis?; and (ii) how are the unmarked and marked constructions of Minangkabaunese functionally used in communication in its speech community? The data presented in this article are the basic-clause constructions which were collected through the execution of a field research in West-Sumatera and supported by a library study. The result of data analysis reveals that the non-verbal grammatical constructions without copula are the formal and functional unmarked constructions in Minangkabaunese. Meanwhile, the constructions with copula are those of formaly and functionally marked.[1] A main local language originally spoken by Minangkabaunese in West Sumatera, Indonesia